The role of traditional market in the traditional Islamic cities : case studies of Tebriz Bazaar and grand Bazaar Tehran - Utaberta, Nangkula; Sabil, Azmal; Asif, Nayeem; Zhengan, Tan; Kiat, Aw Tai (Science Publishing Corporation, 2019)
Trade has been regard as the most important form of social exchange, it is one of main activities of humans, an activity which establish at specific spaces and places called Bazaar. As a traditional public space in Islamic cities, bazaar has always been a great section of commercial activities in urban life. Despite of that, a bazaar also serves as an important platform of social, political, cultural and religious activities. Islamic cities are distinguished from all cities of different historical periods by Bazaar. Bazaars are crucial in giving a sense of integrity to the concept of traditional Islamic cities. Bazaars provide coherence among various parts of cities, such as residential areas, so as socio-economical, political and trade centers. This conditions indicates that bazaars play important roles in traditional Islamic cities : 1. they interconnect different parts of the city's structure physically: and 2. bazaars play a crucial role in a city's social, political, and cultural structure that bring unity among citizens and developments of city. Bazaars serve as an element that connecting the main urban functions and promise the city's economic and social life. Therefore, implementing development plans that would provide bazaars better integration in relation to the city as a whole is necessary. The aim for this research is to explain the role of bazaars in terms of socio-economic and politics in traditional Islamic cities. Also, a general look on the effect of modernization to traditional bazaar. Accordingly, the most important questions for this research are: 1. What is the socio-economical and political role of bazaars in traditional Islamic cities? 2. How do bazaars play out their respective role in the integration of these cities? 3. What is the aftermath of urban modernization to traditional bazaar?